Kurikulum Berbasis Sosio-Saintifik dalam Pembelajaran Biologi - Nursyada, Arsya Putri; Fadilah, Siti Nur; Auranazwa, Kaila; Piyas Lejar Wangi, Raden Rara; Hidayat, Nadia Putri; Ramadhani, Nolla; Usman, Usman (Innovative: Journal Of Social Science Research, 2025)
The implementation of a socio-scientific issues (SSI)-based curriculum in biology education is a response to the demands of 21st-century learning. This curriculum integrates relevant and current social issues with scientific concepts to enhance students' critical thinking skills, scientific literacy, and their ability to make scientifically and ethically informed decisions. This paper adopts the Systematic Literature Review (SLR) method by analyzing various journals and research findings related to the application of the SSI approach in biology education. The results of the review indicate that this approach effectively increases student engagement in learning, develops scientific argumentation skills, and fosters social awareness and concern for environmental and societal issues. Therefore, the socio-scientific-based curriculum is considered an innovative and contextual strategy to support the development of 21st-century competencies in students.